2012
DOI: 10.1186/1471-244x-12-223
|View full text |Cite
|
Sign up to set email alerts
|

Rates of undiagnosed attention deficit hyperactivity disorder in London drug and alcohol detoxification units

Abstract: BackgroundADHD is a common childhood onset mental health disorder that persists into adulthood in two-thirds of cases. One of the most prevalent and impairing comorbidities of ADHD in adults are substance use disorders. We estimate rates of ADHD in patients with substance abuse disorders and delineate impairment in the co-morbid group.MethodScreening for ADHD followed by a research diagnostic interview in people attending in-patient drug and alcohol detoxification units.ResultsWe estimated prevalence of undiag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 31 publications
4
65
0
Order By: Relevance
“…Similar findings were reported by Ohlmeier et al, who observed that habit-forming illnesses can be associated with a high comorbidity with ADHD, expressed in the form of alcohol misuse [10]. In a study conducted by Huntley et al, in 226 alcohol-dependent individuals, 27 (12%) reported with untreated ADHD [21]. In a recent meta-analysis conducted by van de Glind et al, the prevalence rate of ADHD was reported to be approximately 23.3% in patients with SUD seeking treatment [22].…”
Section: Discussionsupporting
confidence: 84%
“…Similar findings were reported by Ohlmeier et al, who observed that habit-forming illnesses can be associated with a high comorbidity with ADHD, expressed in the form of alcohol misuse [10]. In a study conducted by Huntley et al, in 226 alcohol-dependent individuals, 27 (12%) reported with untreated ADHD [21]. In a recent meta-analysis conducted by van de Glind et al, the prevalence rate of ADHD was reported to be approximately 23.3% in patients with SUD seeking treatment [22].…”
Section: Discussionsupporting
confidence: 84%
“…This observation can be considered as a limitation of the present study. Another limitation may be that retrospective recall of childhood ADHD symptoms is particularly challenging in populations with AUD due to impaired memory and the often complex histories with adverse psychosocial risk factors for the development of behavioral problems (25).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with SUD and ADHD had significantly higher self-rated impairments across several domains of daily life, as well as higher rates of substance abuse and alcohol consumption, suicide attempts, and depression (25). Patients with AUD and ADHD comorbidity relapse to AUD on average 2.7 months earlier than patients without ADHD (26,27).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, untreated hyperactive boys with ADHD are at increased risk of substance use disorders and impairment. 11 The burden of ADHD must be analyzed not only in an individual context, but also from a collective standpoint. The economic consequences of the lack of ADHD treatment for society can result in very high losses.…”
Section: Introductionmentioning
confidence: 99%